Empowering the Digital Generation: Enhancing Financial Literacy and Saving Behavior among Youth - Cliford Racelino Ratulangi; Lazarus Suyatno Vianney; Raymond Piring; Gabriela Karen Tuuk; Eridawaty Siagian; Mison Towolom; Tiara Tiara (Al-Qalam Institute, 2026)
This community service program aimed to improve students' digital financial literacy and strengthen saving behavior in the digital era by enhancing their understanding of financial planning, responsible financial management, and the safe use of digital financial services. The program employed a participatory educational approach through counseling sessions, interactive discussions, simulations, and hands-on practice using simple financial applications. The educational materials covered saving concepts, budgeting strategies, digital financial literacy, cybersecurity awareness, and responsible financial decision-making. Program evaluation was conducted using pre- and post-test methods, combined with direct observation, to measure changes in students' knowledge and behavior. The results indicated significant improvements in students' understanding of financial management, awareness of digital transaction security, and ability to utilize simple financial applications responsibly. In addition, students demonstrated stronger motivation to develop saving habits and manage their finances more independently. These findings imply that community-based digital financial literacy education plays an important role in preparing young people to face economic challenges wisely and responsibly in the rapidly evolving digital era.